International Experience with Contractor Driven BOT Concessions - Vestergaard, Jens (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
The BOT approach to building and financing infrastructure projects has been used for, among others, toll roads and bridges, power plants, port facilities, transmission lines and water supply systems. A number of concessions are contractor drive. The paper lists a set of best international BOT practices and a case has been designed to illustrate the points made.